Pengaturan Hukum Positif Di Indonesia Terkait Promosi Judi Online Di Media Sosial - Davin Gerald Parsaoran Silalahi; Ismunarno Ismunarno; Diana Lukitasari (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This article analyzes the criminal offense of promoting online gambling, which is currently widespread on social media. The purpose of this article is to understand the legal frameworks regarding online gambling promotion on social media. The findings indicate that the regulations are found in Article 303 of the Indonesian Criminal Code (KUHP), Article 303 Bis, Article 426 of the New Indonesian Criminal Code (KUHP Baru), and Article 27 paragraph 2, Article 427 of the New Indonesian Criminal Code (KUHP Baru), and Article 45 paragraph 3 of the Indonesian Information Technology Law (UU ITE). The research method used in this writing is legal normative research with a statutory approach and a case approach. The legal sources in this research are primary and secondary legal sources, based on various regulations and various journals and academic writings. The result of the research is that within the online gambling regulations, there is a loophole, which is referred to as the "license" in the KUHP. The online gambling regulations in the Indonesian Information Technology Law are already in accordance with this.